Identifikasi bentuk partisipasi masyarakat Dalam pelaksanaan program Peningkatan kualitas permukiman Studi Kasus : Pada Pelaksanaan Program PLPBK di Permukiman Masyarakat Berpenghasilan Rendah di Kelurahan Tenilo Kota Gorontalo - Mochamad Athar Jantu (Gorontalo Journal of Infrastructure and Science Engineering, 2018)
The participation of the community in an implementation of the program or activity greatly affects the success of the program. This participation itself was born because of the factors from inside and outside the individual as members of that community group. This writing is based on a study that takes place in low-income community settlements in Tenilo RT II / RW II Kelota Kelota Gorontalo, Gorontalo Province with the aim of identifying the forms of community participation as well as the factors that influence the participation of the community in the implementation of the quality improvement program which is part of the Community-Based Settlement Environment Management (PLPBK) program by the government in the National Urban Empowerment Community Empowerment Program (PNPM-Mandiri Urban). The method used in this research is by qualitative analysis approach to analyze the primary and secondary data. The study finds that the form of community participation in the implementation of the program of improving the quality of settlements of low income community groups in Tenilo RT II / RW II Kelota District Gorontalo in the form of energy and goods . Internal factors that influence are gender, education, occupation, age, and income, while external factors as the incentive is the willingness, ability and opportunity.